1 Immanent anthropology: a comparative study of 'process' in contemporary France. (April 2014) - Hodges, Matt
Abstract : This paper presents a comparative critique of the 'processual temporalities' which infuse both social‐scientific theorizing and selected Western cultural practices. Through study of a public‐private partnership which emerged from a biotechnology project devised for producing 'self‐cloning' maize for resource‐poor farmers, I analyse how processual temporalities were central to re‐gearing knowledge practices towards market‐orientated solutions. In a study of characterizations of the 'state of flux' which affects life in a French peri‐urban village, I explore how processualism is identified as a component of a metropolitan hegemony which villagers 'resist' through idealizing 'enduring temporalities' of cultural practice. Drawing on Arendt and Deleuze, I analyse processualism as a dominant contemporary chronotope, mediating and disciplining conflictive temporalities and practices, underwriting economic projects of deterritorialization and restructuring – whose idiom is also prominent in social‐scientific paradigms. I substitute an 'immanent anthropology', which advocates a non‐transcendental ontology of cultural practice and analysis – displacing anthropological analysis onto a polychronic temporal foundation.